BALANCE-SHEET FORM AND CLASSIFICATION IN CORPORATE REPORTS. - Fjeld, E. I. (The Accounting Review, 1936)
The article focuses on balance-sheet form and classification in corporate reports. According to writers of accounting theory, there are two generally accepted forms for the presentation of the balance sheet, the account form and the report form. The account form presents the two sides as in a ledger account, with the assets on the left and the liabilities and net worth on the right side. The report form presents the liabilities and net worth immediately below the assets, in a narrative form. The account form is probably the more convenient of the two because, when it is properly set up, it brings into their proper relationships those sections of a balance sheet which are compared, such as current assets with current liabilities and fixed assets with fixed liabilities. There is little choice between the account and report forms of balance sheet set-up, if proper classification and sequence are observed, both forms then yielding exactly the same information. The length of the balance sheet, however, is a factor in the decision as to form, for it seems to be the accepted principle that it should all appear on one page, or two opposite pages, so that one has the entire statement before him.